Simulasi Kinerja Jaringan Nirkabel IEEE-802.11a dan IEEE-802.11g Menggunakan NS-2 - Helm Fitriawan; Amri Wahyudin (Universitas Syiah Kuala, 2013)
Wireless network uses transmission media based on radio waves. This type of networks is mainly useddue to its efficiency and mobility in data exchanging. This paper reports the modeling and simulation of wirelessnetworks based on Cisco Aironet 1130ag access point devices with IEEE 802.11a and IEEE 802.11g standards. Themodeling and simulation are performed using network simulator version 2 (NS-2) that is installed on operationsystem Linux Ubuntu v.10.10. The NS-2 is commonly used and works well in numerous types of network simulation. From simulation, we obtain quality of service parameters by employing several simulation scenarios in terms ofnumber of nodes, distances, and packet data sizes. It can be concluded from simulation results that the IEEE 802.11gnetworks transfer data with better quality than those of IEEE 802.11a networks. Furthermore, the IEEE 802.11gnetworks provide a higher throughput, with smaller amount of delay and packet loss percentage compared to thoseof IEEE 802.11a networks.